2016
DOI: 10.1590/0102-778620130001
|View full text |Cite
|
Sign up to set email alerts
|

Tendências de Índices de Extremos Climáticos para o Estado do Amazonas e suas Relações com a TSM dos Oceanos Tropicais

Abstract: Esse estudo teve como objetivo principal analisar as tendências de onze índices de extremos climáticos dependentes da precipitação diária para o Estado do Amazonas, dividindo-o em quatro mesorregiões, bem como, analisar suas relações com as anomalias de TSM nos Oceanos Pacífico (ENOS) e Atlântico (Dipolo do Atlântico). Os dados de precipitação pluviométrica diários, para o período de 1970-2010 IntroduçãoEventos climáticos extremos podem ocorrer de muitas formas diferentes, por exemplo, como inundações, secas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(17 reference statements)
1
2
0
4
Order By: Relevance
“…These temperature increases may be associated with a reduction in evapotranspiration and soil heat fluxes, as well as higher albedo and sensible heat fluxes, affecting water and energy balance in the AMZ (Almeida et al, 2017). As to precipitation indices, they mostly increased during the DJF and MAM periods, as previously shown by Santos et al (2016a;2016b), who identified that the most intense precipitation extremes take place during the autumn and that the rainy season in this subregion is associated with the ITCZ (De Souza et al, 2005;De Souza and Rocha, 2006). Extreme precipitation events are also associated with CSL, which are more frequent during the winter and the autumn.…”
Section: Discussionsupporting
confidence: 55%
“…These temperature increases may be associated with a reduction in evapotranspiration and soil heat fluxes, as well as higher albedo and sensible heat fluxes, affecting water and energy balance in the AMZ (Almeida et al, 2017). As to precipitation indices, they mostly increased during the DJF and MAM periods, as previously shown by Santos et al (2016a;2016b), who identified that the most intense precipitation extremes take place during the autumn and that the rainy season in this subregion is associated with the ITCZ (De Souza et al, 2005;De Souza and Rocha, 2006). Extreme precipitation events are also associated with CSL, which are more frequent during the winter and the autumn.…”
Section: Discussionsupporting
confidence: 55%
“…A massa equatorial continental (mEc), originária da Amazônia, é caracterizada por ser quente e úmida e levar umidade durante o verão para esta região do Brasil, os índices de extremos climáticos nesta localidade mostraram sofrer influências das anomalias dos oceanos Pacífico e Atlântico (Santos et. al., 2012;Santos et. al., 2016), o que pode contribuir de forma indireta para aumento ou diminuição das chuvas no Mato Grosso.…”
Section: Extremos De Precipitação E Anomalia De Tsmunclassified
“…Logo, Santos et al (2016) consideram que é respeitável conhecer a variação pluviométrica da região amazônica, bem como a precipitação e sua relação com o funcionamento da floresta. Salientam também que os riscos emergentes das mudanças no ciclo hidrológico, decorrentes de processos vinculados a forças motrizes como extração de minérios, de madeiras, pecuária e produção de energia, atuais modelos venerados de desenvolvimento econômico do Sudeste paraense, constituem uma ameaça para o meio ambiente e para a saúde humana, principalmente, a nível local.…”
Section: Introductionunclassified